Improvement in Entrapment Efficiency and In Vitro Digestion Stability of Lutein by Zein Nanocarriers with Pepsin Hydrolysis - Yan Jiao; He Han; Ying Chang; Dajing Li; Asad Riaz (Journal of Food Quality)
Zein is one of the popular bioactive carriers and play critical roles in the promotion of stability, absorption, and utilization of the nutrients and bioactive ingredients. The application of zein delivery systems for the encapsulation of bioactive ingredients has recently gained increasing interest. The aim of this work was to modify zein by pepsin and prepare the lutein-loaded zein nanoparticle (LZN) and the lutein-loaded zein hydrolysate nanoparticle (LZHN), respectively. The effects of zein hydrolysation on entrapment efficiency and in vitro digestion stability of lutein were also evaluated in this study. Hydrolysation of zein by the pepsin has important effects on lutein embedding. The optimal hydrolysis conditions, including the pepsin concentration (1.5%), temperature (55°C), and time (4 h), enhanced the entrapment efficiency (EE) of lutein by 93.82 ± 2.82% as compared to 85.18 ± 3.28% of the untreated zein, respectively. In contrast to LZN, LZHN had better structural characteristics, the average particle size decreases from 158.40 ± 3.22 nm to 112.2 ± 1.56 nm, and LZHN showed better dispersivity and zeta potential. The stability and release assays in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) showed that hydrolyzed zein nanocarriers by pepsin improved the digestion stability and promoted the release of lutein under gastrointestinal digestive conditions. These results suggest that hydrolyzed zein with pepsin may act as an effective carrier for lutein delivery and shows many potential advantages compared with the zein.